122 GHz Patch Antenna Designs by Using BCB Above SiGe BiCMOS wafer process for system-on-chip applications - Wang, Ruoyu; Kaynak, Mehmet; Sun, Yaoming; Borngräber, Johannes; Beer, Stefan; Goettel, B.; Scheytt, Christoph (24th Annual IEEE International Symposium on Personal, Indoor and Mobile Radio Communications)
Two half-wavelength 122 GHz patch antennas were designed and manufactured by using Benzocyclobutene (BCB) as a dielectric layer above the SiGe BiCMOS wafer. It enables the full integration of the millimeter-wave transceiver circuits and the antennas on a single chip to simplify the packaging procedure at millimeter-wave frequencies, thereby reducing the cost. The two patch antennas are fed by different feeding methods, i.e. microstrip transmission line direct feed and proximity-coupled feed. They exhibit similar performance and offer the flexibility of designing the interconnects (feed lines routing) between the circuits and the antennas within the very limited chip area. The measured gain is 3.4 dBi at 122.5 GHz (the center frequency of the ISM band of 122-123 GHz) for both designs with a simulated efficiency of about 50%.

A 125-GHz Permittivity Sensor With Read-Out Circuit in a 250-nm SiGe BiCMOS Technology - Laemmle, Benjamin; Schmalz, Klaus; Scheytt, Christoph; Weigel, Robert; Kissinger, Dietmar (Microwave Theory and Techniques, IEEE Transactions on)
In this paper, an integrated dielectric sensor with a read-out circuit in an unmodified SiGe BiCMOS technology at 125 GHz is presented. The sensor consists of a 500-μm shorted half-wave coplanar-waveguide transmission line in the uppermost metal layer of the silicon process, while the read-out is obtained by reflection coefficient measurement with an integrated reflectometer and a signal source. The reflectometer is verified with a circuit breakout including an integrated dummy sensor. The reflectometer is able to measure the phase of the reflection coefficient from 117 to 134 GHz with a resolution of 0.1° and a standard deviation of 0.082°. The integrated sensor with the reflectometer circuit have been fabricated in a 190-GHz fT SiGe:C BiCMOS technology. It spans an area of 1.4 mm 2 and consumes 75 mA from a 3.3-V supply. The circuit has been assembled on a printed circuit board for characterization by immersion into test liquids. The sensor is controlled by a controller board and a personal computer enabling a measurement time of up to 1 ms per frequency point. Functionality of the sensor is demonstrated from 118 to 133 GHz with immersion of the sensor into different binary methanol-ethanol mixtures, showing good correlation between theory and measurement. The sensor shows a standard deviation of the measured phase of 0.220° and is able to detect a difference in ε' r of 0.0125

Neue Ansätze für miniaturisierte, hochintegrierte Abstands-, Geschwindigkeits- und Drehwinkelsensoren - Scheytt, Christoph; Grau, Günter (Wissenschaftsforum 2013, Intelligente Technische Systeme, Heinz Nixdorf Institut)

Introduction to Integrated mm‐Wave Sensors - Scheytt, Christoph (System, IC and Integrated Antenna Design for Miniaturized, Millimeter-wave Radar Sensors)

220–250-GHz Phased-Array Circuits in 0.13- μ\hbox m SiGe BiCMOS Technology - Elkhouly, Mohamed; Glisic, Srdjan; Meliani, Chafik; Ellinger, Frank; Scheytt, Christoph (Microwave Theory and Techniques, IEEE Transactions on)
This paper describes the design of D-band phased-array circuits in 0.25 μm technology. The first part describes the design of the passive components which are used in the phased-array systems such as balun, Wilkinson divider and branch-line coupler. A millimeter-wave vector-modulator is designed to support both amplitude and phase control for beam-forming applications. In the second part the designed circuits are integrated together to form a two channel 110-130 GHz phased-array chip. Each channel exhibits 360° phase control with 15 dB of amplitude control range and gain of -10 dB. The entire chip draws 45 mA from 3.3 V supply. The millimeter-wave phase shifting and the low-power consumption makes it ideal for highly integrated scalable beam-forming systems for both imaging and communication.

Analysis and minimization of substrate spurs in fractional-N frequency synthesizers - Osmany, Sabbir Ahmed; Herzel, Frank; Scheytt, Christoph (Analog Integrated Circuits and Signal Processing)
This paper analyses substrate-related spurious tones in fractional-N phase- locked loops with integrated VCOs. Spur positions are calculated and experimentally verified as a function of the divider ratios of prescaler and programmable divider. For an integrated wideband PLL in SiGe BiCMOS technology the spur power levels are measured and compared with theoretical expectations. The power in these spurs is minimized by layout techniques shielding the reference input buffer. Spur minimization by using a variable reference frequency is experimentally demonstrated. Based on this observation, a programmable integer-N PLL for driving the fractional-N synthesizer is suggested to reduce the worst-case spur level significantly. Index Terms — Fractional-N, frequency synthesizers, fractional spurs, substrate spurs, phase-locked loops (PLLs), phase noise.

Flip-Chip Package with Integrated Antenna on a Polyimide Substrate for a 122-GHz Bistatic Radar IC - Beer, Stefan; Girma, Mekdes Gebresilassie; Sun, Yaoming; Winkler, Wolfgang; Debski, Wojciech; Paaso, Jaska; Kunkel, Gerhard; Scheytt, Christoph; Hasch, Jürgen; Zwick, Thomas (7th EUROPEAN CONFERENCE ON ANTENNAS AND PROPAGATION)
This paper presents the packaging technology and the integrated antenna design for a miniaturized 122-GHz radar sensor. The package layout and the assembly process are shortly explained. Measurements of the antenna including the flip chip interconnect are presented that have been achieved by replacing the IC with a dummy chip that only contains a through-line. Afterwards, radiation pattern measurements are shown that were recorded using the radar sensor as transmitter. Finally, details of the fully integrated radar sensor are given, together with results of the first Doppler measurements.

Computing time investigations for variational multirate integration - Gail, T.; Leyendecker, S.; Ober-Blöbaum, Sina (Proceedings of Applied Mathematics and Mechanics)

Set oriented methods for the numerical treatment of multi-objective optimization problems - Schütze, O.; Witting, K.; Ober-Blöbaum, Sina; Dellnitz, M.; Tantar, Emilia (EVOLVE - A Bridge Between Probability, Set Oriented Numerics, and Evolutionary Computation)

A variational approach to multirate integration for constrained systems - Leyendecker, S.; Ober-Blöbaum, Sina (Jean-Claude Samin and Paul Fisette, editors, Multibody Dynamics)